The Relationship Between Knowledge Of Balanced Nutrition And Nutritional Status Among Students - Izmi Arisa Putri Lubis (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
The nutritional status of students can be influenced by their knowledge of balanced nutrition. This study aimed to analyze the relationship between knowledge of balanced nutrition and the nutritional status of students at SMK SPP SNAKMA Muhammadiyah Tanjung Anom. An analytical observational method with a cross-sectional study approach was applied. The research was conducted from November 2022 to June 2023 at SMK SPP SNAKMA Muhammadiyah Tanjung Anom. The study population comprised X and XI grade students, with a sample size of 90 students selected through systematic random sampling. The relationship between variables was assessed using the Chi-Square test with α = 0.001. The findings revealed that a significant proportion of respondents had good knowledge of balanced nutrition (67.8%) and good nutritional status (78.9%). The conclusion of this research is that there is a significant relationship between knowledge of balanced nutrition and the nutritional status of students at SMK SPP SNAKMA Muhammadiyah Tanjung Anom, with a P-value of 0.001 (P<0.05). Students are encouraged to read more books or seek journal references related to balanced nutrition to enhance their knowledge in this area.